2017
DOI: 10.1016/j.japh.2016.12.070
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' readiness to provide naloxone in community pharmacies in West Virginia

Abstract: Objectives The objective of this study is to assess West Virginia (WV) pharmacists’ stocking and dispensing practices of opioid-related medications and to identify the educational needs relating to providing naloxone in community pharmacies. Design A cross-sectional, anonymous, 49-item survey was created and validated to assess the educational needs of WV community pharmacists. Setting and participants The data collection instrument was administered to 266 pharmacists currently licensed in WV at six contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 16 publications
2
110
0
Order By: Relevance
“…21 In the second study, researchers assessed West Virginia community-based pharmacy practices regarding buprenorphine product stocking and dispensing. 22 There are still limited data evaluating U.S. community-based pharmacists' knowledge and perceptions regarding MAT. Investigating this population may yield beneficial data to enhance MAT access for patients with OUD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In the second study, researchers assessed West Virginia community-based pharmacy practices regarding buprenorphine product stocking and dispensing. 22 There are still limited data evaluating U.S. community-based pharmacists' knowledge and perceptions regarding MAT. Investigating this population may yield beneficial data to enhance MAT access for patients with OUD.…”
Section: Resultsmentioning
confidence: 99%
“…As this U.S. study's population can only dispense buprenorphine products for MAT, these results are similar. In the United States, though Thornton et al 22 did not address perceptions specifically, respondents estimated that a mean of 23.6 (26.8 standard deviation) patients out of 100 filling buprenorphine prescriptions misused or abused the medication. 22 This similarity, internationally and in the United States, describes a common concern and a potentially negative perception held by communitybased pharmacists when providing care to patients with OUD-specifically that the patients will misuse buprenorphine products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that pharmacists can effectively engage patients with OUD to improve their outcomes . In turn, patients have reported positive attitudes when a pharmacist was included in their OUD treatment care …”
Section: Introductionmentioning
confidence: 99%
“…22,23 In turn, patients have reported positive attitudes when a pharmacist was included in their OUD treatment care. 24,25 We conducted a narrative literature review to highlight several pharmacist-driven practices that provide a broad range of prevention, harm reduction, treatment, and recovery services to patients affected or potentially affected by the opioid crisis.…”
Section: Introductionmentioning
confidence: 99%